PL.25 Prenatal Diagnosis of Congenital Heart Disease: Effect on Labour Progress and Mode of Delivery. (26th April 2013) - McTiernan, A; Farrell, S; Walsh, CA; Mulcahy, C; McMahon, C; McAuliffe, FM
Abstract : Objective: To compare mode of delivery in fetuses with known congenital heart disease (CHD) versus the background rate in non-anomalous fetuses. Methods: We examined all cases of prenatally-diagnosed CHD over the 5-year study period, 2007–2011. Data were extracted from computerised patient records. Control data for non-anomalous fetuses were obtained from published hospital records for 2007. Categorical data were analysed using Fisher's exact test (5% level significant). Results: We identified 242 cases of prenatally-diagnosed CHD over the study period. We excluded 25 lethal karyotypes, 7 miscarriages and 1 termination. Of the remaining 209 cases, complete labour records were available for 158 women. There were 146 live births (92%) and 12 antepartum stillbirths at ≥24 weeks (8%). Of the live-born infants with CHD, the perinatal mortality rate was 41 per 1, 000. Extra-cardiac defects and non-lethal karyotypic abnormalities were present in 22% (n = 34) and 11% (n = 18) of the cohort respectively. Overall, 23% (34/146) underwent elective caesarean section (CS). The remaining 112 women had a trial of labour, with a 13% (n = 15) intrapartum CS rate. The rate of intrapartum CS for nulliparous women with known CHD was 18% (8/45), which was not different to the rate in nulliparous controls in 2007 (13%; 432/3324; p = 0.27). The equivalent rate in multiparous women was 10% (7/67) in CHD versus 2.4% (80/3392) in controls without previous CS (p = 0.0013). Conclusions: The rate of intrapartum CS in fetuses with known CHD is not different to the background rate in nulliparous women but is increased in multips.